ITRAQ‐based proteomic analysis of dioscin on human HCT‐116 colon cancer cells. Issue 1 (13th January 2014) - Chen, Hao; Xu, Lina; Yin, Lianhong; Xu, Youwei; Han, Xu; Qi, Yan; Zhao, Yanyan; Liu, Kexin; Peng, Jinyong
Abstract : Dioscin shows various pharmacological effects. However, its activity on colorectal cancer is still unknown. The present work showed that dioscin significantly inhibited cell proliferation on human HCT‐116 colon cancer cells, and affected Ca 2+ release and ROS generation. The content of nitric oxide (NO) and its producer inducible NO synthase (iNOS) associated with DNA damage and aberrant cell signaling were assayed using the kits. DNA damage and cell apoptosis caused by dioscin were also analyzed through single‐cell gel electrophoresis and in situ terminal deoxynucleotidyl transferase dUTP nick‐end labeling assays. The results showed that dioscin increased the levels of NO and inducible NO synthase. The comet length in dioscin‐treated groups was much longer than that of the control group, and the number of terminal deoxynucleotidyl transferase dUTP nick‐end labeling positive cells (apoptotic cells) was significantly increased by the compound ( p < 0.01). Furthermore, dioscin caused mitochondrial damage and G2/M cell cycle arrest through transmission electron microscopy and flow cytometry analysis, respectively. To study the cytotoxic mechanism of dioscin, an iTRAQ‐based proteomics approach was used. There were 288 significantly different proteins expressed in response to dioscin, which were connected with each other and were involved in different Kyoto Encyclopedia of Genes and Genomes pathways. Then, some differentially expressed proteins involved in oxidative phosphorylation, Wnt, p53, and calcium signaling pathways were validated by Western blotting and quantitative real‐time PCR assays. Our work elucidates the molecular mechanism of dioscin‐induced cytotoxicity in colon cancer cells, and the identified targets may be useful for treatment of colorectal cancer in future.